2007
DOI: 10.1007/s00428-007-0424-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of automated silver enhanced in situ hybridisation (SISH) and fluorescence ISH (FISH) for the validation of HER2 gene status in breast carcinoma according to the guidelines of the American Society of Clinical Oncology and the College of American Pathologists

Abstract: HER2 is an important tumour marker in breast cancer. However, there is controversy regarding which method reliably measures HER2 status. This study evaluates the concordance between HER2 gene amplification in invasive breast cancer determined by fluorescence in situ hybridisation (FISH) and a new silver enhanced in situ hybridisation (SISH) technique. Ninety-nine cases were analysed by direct-labelled manual FISH (PathVysion(R), Abbott/Vysis) and bright field automated SISH (INFORM(R), Ventana). For comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
96
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 24 publications
(20 reference statements)
10
96
0
3
Order By: Relevance
“…This light-microscopy-based in situ hybridisation technique may be superior to conventional fluorescence in situ hybridisation for the investigation of small amplified tumour cell foci. 18,21,22 This phenomenon frequently occurs in oesophagogastric carcinomas 1,3,23 and can readily be recognised by this method. We have compared bright field double in situ hybridisation data with fluorescence in situ hybridisation data from a previously published study 12 and found a significant correlation between bright field double in situ hybridisation and both conventional fluorescence in situ hybridisation and the more complex but more sensitive 3D fluorescence in situ hybridisation.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This light-microscopy-based in situ hybridisation technique may be superior to conventional fluorescence in situ hybridisation for the investigation of small amplified tumour cell foci. 18,21,22 This phenomenon frequently occurs in oesophagogastric carcinomas 1,3,23 and can readily be recognised by this method. We have compared bright field double in situ hybridisation data with fluorescence in situ hybridisation data from a previously published study 12 and found a significant correlation between bright field double in situ hybridisation and both conventional fluorescence in situ hybridisation and the more complex but more sensitive 3D fluorescence in situ hybridisation.…”
Section: Discussionmentioning
confidence: 91%
“…For breast cancer, similar observations were reported by others who described a high concordance in the assessment of ErbB2 amplification between fluorescence in situ hybridisation and the light-microscopy-based techniques of silver in situ hybridisation and bright field double in situ hybridisation, respectively, with advantages in terms of handling, orientation within the slides and in cases of intratumoral heterogeneity for bright field double in situ hybridisation. 21 For the application of immunohistochemical staining and in situ hybridisation, we used tissue microarrays, which contained cores from a total of 142 oesophageal adenocarcinomas from which extensive clinico-pathological documentation was available. Unfortunately, we could not use one tissue microarray for the comparison of all methods because tissue microarrays constructed at two different time points were required.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies reporting on concordance rates for HER2 silver enhanced in situ hybridization vs. fluorescence in situ hybridization of 96% (k ¼ 0.75, 95% CI) and 99%. 13,27 Additionally, we assessed the EGFR gene status with a semiquantitative polymerase chain reactionbased assay and compared the results with silver enhanced in situ hybridization. Semiquantitative polymerase chain reaction-based assay results concurred excellent with silver enhanced in situ hybridization findings (Po0.001) and showed high association with EGFR silver enhanced in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…After washing the EGFR and chromosome 7 dinitrophenol-labelled probes were visualized using the rabbit anti-dinitrophenol antibody and the ultraVIEW silver SISH Detection Kit. For details see Dietel et al 13 The silver precipitation was deposited in the nuclei and a single copy of the EGFR gene or the centromere 7 was visualized as a black dot. After counterstaining 60 tumour cells, nuclei were evaluated in three different areas (20 nuclei each).…”
Section: Silver Enhanced In Situ Hybridizationmentioning
confidence: 99%
“…[8][9][10][11] SISH was implemented more recently and three studies reported a 97, 96 and 87% concordance between SISH and FISH results on excision samples [12][13][14] taking into account that discordant cases could be partly explained by intratumor heterogeneity of amplification. One study showed an 89% concordance of SISH results between surgical specimens and core-needle biopsies but the number of studied cases was limited (n ¼ 56).…”
mentioning
confidence: 99%